Prolegomena to Bentley's Unfinished New Testament Project. - Yi, An-Ting; Krans, Jan; Lietaert Peerbolte, Bert Jan (Novum Testamentum, 2020)
It is well known that the eighteenth-century classical scholar Richard Bentley once announced but never finished an ambitious project for a critical NT edition. What is less well known is that numerous entries of his archive have been preserved in Wren Library of Trinity College (TCL), Cambridge, until today. This article provides some prolegomena to a comprehensive enquiry into Bentley's unfinished NT project. It includes an updated summary of the archive, relevant secondary literature, a few examples for illustration, and on the basis of all this, some suggestions for future study.